Implementation of the Mata Elang Pembangunan Application in Supporting SPBE-Based ASN Management in South Lampung Regency - Ence Sopyan; M. Reza Andrea Putra (Priviet Social Sciences Journal, 2026)
Digital transformation through Indonesia's Electronic-Based Government System (SPBE) has intensified pressure on regional governments to deploy integrated digital platforms. The South Lampung Regency Government developed the Mata Elang Pembangunan application as a cross-OPD development planning data integration system, aligned with the One Data Indonesia policy. This study examines how Civil State Apparatus or Aparatur Sipil Negara (ASN) engage with this application within SPBE governance frameworks specifically, how it shapes ASN participation in planning workflows, inter-OPD coordination, and data-based decision-making processes. Using a qualitative case study design, data were collected through semi-structured in-depth interviews with 15 informants (five ASN users, three Diskominfo administrators, four Bappeda planning officials, and three OPD heads), direct observation, and documentary analysis. Data were coded inductively and analyzed using an interactive model. An implementation framework with four dimensions institutional commitment, technical functionality, human capacity, and policy alignment organized the analysis. Findings show that the application is progressively embedded in planning workflows and has improved inter-OPD coordination and data accessibility. However, significant challenges persist: uneven ASN digital literacy, data integration failures with legacy systems, inadequate ongoing training, and weak linkages between application use and performance management. The paper argues that these are organizational problems requiring structural responses, not peripheral issues, and that the application's trajectory while broadly positive remains fragile without addressing these constraints. This study contributes empirical insights to the literature on SPBE implementation at the Indonesian local government level and calls for a sharper research agenda on the human and organizational dimensions of digital planning system adoption.